PENERAPAN TERAPI PURSED LIPS BREATHING (PERNAPASAN MELALUI BIBIR) DENGAN MODIFIKASI MENIUP BALON TERHADAP STATUS OKSIGENASI PADA ANAK USIA PRA SEKOLAH (3-6 TAHUN) DENGAN PNEUMONIA DI RUANG RAWAMERTA RSUD KARAWANG - Wirdan Fauzi Rahman; Serly, Serly; Neng Lia Natalia (Bajang Institute, 2024)
Pneumonia is a major cause of morbidity and mortality in children under five years of age. This condition causes impaired gas exchange and decreased oxygen saturation. A non-pharmacological effort that can be done to improve oxygenation is Pursed Lips Breathing (PLB) therapy. In preschool children, this therapy can be modified through balloon blowing activities to make it more interesting and easier to do. To determine the effect of Pursed Lips Breathing therapy with balloon blowing modifications on oxygenation status in preschool children with pneumonia in the Rawamerta Ward, Karawang Regional Hospital. This study used a pre-experimental one group pretest-posttest design. The sample consisted of 16 children aged 3–6 years who met the inclusion criteria. The intervention was carried out by children inhaling through the nose and exhaling through pursed lips while blowing a balloon for 5 times per session, twice a day for three days. Oxygen saturation measurements were carried out using a pulse oximeter before and after the intervention. Data analysis used the Wilcoxon test. The average oxygen saturation value before therapy was 92.18%, and after therapy it increased to 96.50%. The Wilcoxon test showed a p-value of 0.002 (p < 0.05), indicating a significant effect between the application of Pursed Lips Breathing therapy, modified by blowing a balloon, and improving oxygenation status in preschool children with pneumonia. Conclusion: Pursed Lips Breathing therapy, modified by blowing a balloon, effectively improves oxygenation status in preschool children with pneumonia. This technique can be used as a simple, inexpensive, and enjoyable alternative non-pharmacological intervention for children.